What do we know about our professional self-government of nurses and midwives? Preliminary study - Kolbe, Gilbert; Kryczka, Tomasz (Nursing in the 21st Century, 2021)
WHAT DO WE KNOW ABOUT OUR PROFESSIONAL SELF-GOVERNMENT OF NURSES AND MIDWIVES? PRELIMINARY STUDYIntroduction. Professional self-government is a form of association of persons who practice the same profession, established in order to represent their interests against the state authorities.Aim. The aim of the study was to assess the knowledge of nurses and midwives on their professional self-government and their engagement in its activity.Material and methods. The study was conducted among 1,143 nurses and midwives. An originally designed questionnaire was used. The survey was administered via the Internet. Findings from questionnaires completed by 895 members of the Warsaw Regional Chamber of Nurses were analysed statistically.Results. Nearly 3/4 of respondents had low-to-medium knowledge on their professional self-government. Age and career length were positively correlated with a high level of knowledge.Conclusions. The knowledge of nurses and midwives on their professional self-government and news related to its functioning should be considered unsatisfactory and fragmentary. Further studies to determine the way to convey this knowledge to nurses and midwives are needed in order to expand this knowledge.